Causes of poor outcome in patients admitted with good-grade subarachnoid haemorrhage - Beneš, Vladimír; Jurák, Lubomír; Brabec, Radim; Nechanická, Nina; Šercl, Miroslav; Endrych, Ladislav; Buchvald, Pavel; Suchomel, Petr (Acta neurochirurgica, 2017)
BACKGROUND: Surgical risk in patients with unruptured aneurysms is well known. The relative impact of surgery and natural history of subarachnoid haemorrhage (SAH) on patients in good clinical condition (World Federation of Neurological Surgeons [WFNS] grades 1 and 2) is less well quantified. The aim of this study was to determine causes of poor outcome in patients admitted in good grade SAH. METHODS: A retrospective study of prospectively collected data among WFNS-1 and -2 patients: demographics, SAH and aneurysm-related data, surgical complications and outcome as assesed by the Glasgow Outcome Scale (GOS). Causes of poor outcome (GOS 1-3) were determined. RESULTS: During a 7-year period (2009-15), 56 patients with SAH WFNS-1 (39 patients) or WFNS-2 (17 patients) were treated surgically (21 men, 35 women; mean age, 52.4 years). According to the Fisher scale, 19 patients were grade 1 or 2; 37 patients were grade 3 or 4. Most aneurysms were located at anterior communicating (26) or middle cerebral (15) artery. Altogether, 11 patients (19.6%) achieved GOS 1-3. This was attributed to SAH-related complications in six patients (rebleeding, vasospasm), surgery in four patients (postoperative ischaemia in two, haematoma and ventriculitis in one patient each), grand-mal seizure with aspiration in one patient. Age over 60 years (p = 0.017) and presence of hydrocephalus (p < 0.001) were statistically significant predictors of poor GOS; other variables (e.g. sex, Fisher grade, aneurysm size or location, use of temporary clips, intraoperative rupture, vasospasm) were not significant. CONCLUSIONS: Patients admitted in good-grade SAH achieve favourable outcome following surgical aneurysm repair in the majority of cases. Negative factors include age over 60 years and presence of hydrocephalus. Aneurysm surgery following good-grade SAH still carries a small but significant risk similar to that shown in large multi-institutional trials.
Keywords: senioři; Surgical complication; Middle Aged; mužské pohlaví; Surgical Instruments; subarachnoidální krvácení; Intracranial Aneurysm; Adult; Postoperative Complications; Subarachnoid haemorrhage; ženské pohlaví; chirurgické nástroje; Aneurysm, Ruptured; Humans; Aneurysm; lidé středního věku; prasklé aneurysma; Subarachnoid Hemorrhage; dospělí; intrakraniální aneurysma; Female; Aged; pooperační komplikace; lidé; Male; Outcome